No Evidence of Robust Noun-Referent Associations in German-Learning 6- to 14-Month-Olds - Steil, Jessica N.; Friedrich, Claudia K.; Schild, Ulrike (Frontiers in Psychology, 2021)
Work with the looking-while-listening (LWL-) paradigm suggested that six-month-old English-learning infants associated several labels for common nouns with pictures of their referents: While one distractor picture was present, infants systematically fixated the named target picture. However, recent work revealed constraints of infants’ noun comprehension. The age at which these abilities can be obtained appears to relate to the infants’ familiarity with the talker, the target language, and word frequency differences in target-distractor pairs. Here, we present further data to this newly established field of research. We tested 42 monolingual German-learning infants aged six to 14 months by means of the LWL-paradigm. Infants saw two pictures side-by-side on a screen, whilst an unfamiliar male talker named one of both. Overall, infants did not fixate the target picture more than the distractor picture. In line with previous results, infants’ performance on the task was higher when target and distractor differed within their word frequency - as operationalized by the parental rating of word exposure. Together, our results add further evidence for constraints on early word learning. They point to cross-linguistic differences in early word learning and strengthen the view that infants might use extra-linguistic cues within the stimulus pairing, such as frequency imbalance, to disambiguate between two potential referents.